Análisis descriptivo del comportamiento e importancia de los proveedores y clientes en el proceso de reciclaje para el sector textil en Bogotá D.C. (2021)
In recent years, the textile industry has grown in Colombia and the world, positively impacting the dynamics of employment and the economy of cities. However, the increase in the production and consumption of textiles has triggered several environmental problems, from the manufacturing process to the use of the garments, generating post-industrial and post-consumer waste, which could be recycled or reused to increase the useful life of these products.